Student Experiences and Changing Science Interest When Transitioning from K-12 to College - David E. Reed; Emily C. Kaplita; David A. McKenzie; Rachel A. Jones (MDPI AG, 2022)
Student attitude and involvement in the sciences may be positively or negatively influenced through both formal academic experiences and informal experiences outside the classroom. Researchers have reported that differences in science interest between genders begin early in a student's career and that attitudes towards a particular field of science can be correlated to achievement in that field. In this study, we approach the question of how attitudes towards science have been shaped using college-age students. Survey data from students in similar academic positions were employed to control for differences in cultural and academic progress. Results from a self-reflection survey indicated that general personal interest in both science as a process and field-specific content increased from elementary school through high school until entering college. Differences arose between self-identified genders in student experiences with science, both while in groups and when on their own. Female students had higher rates of participation and enjoyment with science in groups, while male students more frequently enjoyed science alone. Students, regardless of gender, rarely had negative experiences with science outside of the classroom. However, male students' interest in science surpassed female students' during high school. Declining interests in quantitative aspects of science (mathematics and statistics) were more frequently reported by female students and non-STEM majors during and before their college experience. Connecting student attitudes regarding science to their pre-college experiences with science early in their college career may be important to understanding how to best engage all genders, as well as non-STEM majors, in their college science courses.